May material bottlenecks hamper the global energy transition towards the 1.5 °C target?. (November 2022) - Schlichenmaier, Simon; Naegler, Tobias
Abstract: Potentially scarce materials play an important role in many current and emerging technologies needed for a sustainable energy and mobility system. This paper examines the global demand for 25 potentially scarce materials that would result from an energy system that is compatible with the 1.5 °C target. It further analyses the risk for short- and mid-term material shortages. To determine the material requirements, an extensive prospective database was built up on the specific demand of these materials in key technologies. A second database describes the potential development of sub-technology market shares within a technology class. A material flow analysis model was used to determine the annual and cumulative material requirements as well as the recycling potential in the underlying scenario. The results show that production of all materials has to increase, in some cases significantly, in a short period of time to meet the demand for the energy and transportation system. In addition, the cumulative demand for some materials significantly exceeds current reserves and even resources. In particular, lithium (demand increase (DI) more than factor 10, cumulated demand (CD) exceeds reserves up to factor 2), cobalt (DI/CD: <7/<3), and nickel (CD/DI: <2.4/<1.4) for batteries, dysprosium (DI < 8) and neodymium (DI < 1.5) (for permanent magnets (wind turbines and electric motors), and iridium (DI < 2.9) as well as platinum (DI < 1.8) (fuel cells, electrolyzers) are affected. The construction of battery electric and fuel cell electric vehicles thus represents a major driver of the material demand. Depending on the material, shortages can be reduced or delayed by technology substitution, material recycling, technology lifetime extension, increased material efficiency, and a smaller future vehicle stock, but not entirely avoided. Hence, it can be expected that material bottlenecks will result in increasing material prices, at least in the short to medium term. Graphical abstract: Highlights: Defossilisation of energy and transport depends on availability of scarce minerals. Material shortages may occur in particular for Li, Co, Ni, Dy, Nd, and Ir. Shortages can be reduced by appropriate measures, but not entirely avoided. The databases on which the analysis is based are made available for public use.